Rath & Strong’s workout for Six Sigma pocket guide : - Federico, Mary (McGraw-Hill, 2005)
Companies worldwide use Six Sigma to measure and improve performance. Others use WorkOut to get quick bottom-line results and empower their workforce. But few enjoy the enormous success General Electric achieved by combining these approaches. Rath & Strong shows you how to get that synergy, with a handy pocket guide full of charts, checklists, assessment tools, and cases that help you: